Closing the Gap for Electronic Short‐Circuiting: Photosystem I Mixed Monolayers Enable Improved Anisotropic Electron Flow in Biophotovoltaic Devices. Issue 4 (23rd November 2020) - Wang, Panpan; Frank, Anna; Zhao, Fangyuan; Szczesny, Julian; Junqueira, João R. C.; Zacarias, Sónia; Ruff, Adrian; Nowaczyk, Marc M.; Pereira, Inês A. C.; Rögner, Matthias; Conzuelo, Felipe; Schuhmann, Wolfgang
Abstract: Well‐defined assemblies of photosynthetic protein complexes are required for an optimal performance of semi‐artificial energy conversion devices, capable of providing unidirectional electron flow when light‐harvesting proteins are interfaced with electrode surfaces. We present mixed photosystem I (PSI) monolayers constituted of native cyanobacterial PSI trimers in combination with isolated PSI monomers from the same organism. The resulting compact arrangement ensures a high density of photoactive protein complexes per unit area, providing the basis to effectively minimize short‐circuiting processes that typically limit the performance of PSI‐based bioelectrodes. The PSI film is further interfaced with redox polymers for optimal electron transfer, enabling highly efficient light‐induced photocurrent generation. Coupling of the photocathode with a [NiFeSe]‐hydrogenase confirms the possibility to realize light‐induced H2 evolution. Abstract : Towards the development of improved biophotovoltaic devices for solar energy conversion, a mixed monolayer constituted by photosystem I trimers and monomers enables the fabrication of highly efficient biophotoelectrodes by minimizing electronic short‐circuiting processes while at the same time ensuring a high density of photoactive molecules per unit area.